FUNCTIONAL RESERVES OF MEDICAL STUDENTS YEAR 2007–2012 - E. V. Kharlamov; N. M. Popova; I. Y. Gotadze (Медицинский вестник Юга России, 2014)
Purpose: study of the morphofunctional peculiarities of students on the medical faculty/Materials and methods: 62 students of 1st course, studying in the main group of physical education were surveyed. 578 medical control cards of graduates year 2007 – 2012 were analysed. During the survey the following methods were used: Body Type, Artenal Blood Pressure, Pulsometry, ECG diagnostics, Spirography, Stepergometry according to location PWC 170. Calculation method: the adaptive capacity, physical efficiency, MOC (maximum oxygen consumption) and AP (aerobic performance) were calculated.Results: 36% of the students of 1st course in the main physical education group was related to the MaC and MeMaC – types with resistive mechanism of adaptation. 28,5% of female and 32,7% of male graduates had decreased physical efficiency and indicators of life – support.Summary: students of the main group of physical education need to have differentiated programs of physical training, given that the adaptive capacity and body type are taken in to consideration. To determine the individual tolerance to physical stress, 60% of the graduates will need to undergo veloergometry with pulse, blood pressure and ECG being registered and cotrolled.